Electrophysiological and morphological changes in colonic myenteric neurons from chemotherapy‐treated patients: a pilot study. Issue 7 (22nd February 2016) - Carbone, S. E.; Jovanovska, V.; Brookes, S. J. H.; Nurgali, K.
Abstract: Background: Patients receiving anticancer chemotherapy experience a multitude of gastrointestinal side‐effects. However, the causes of these symptoms are uncertain and whether these therapeutics directly affect the enteric nervous system is unknown. Our aim was to determine whether the function and morphology of myenteric neurons are altered in specimens of the colon from chemotherapy‐treated patients. Methods: Colon specimens were compared from chemotherapy‐treated and non‐treated patients following colorectal resections for removal of carcinoma. Intracellular electrophysiological recordings from myenteric neurons and immunohistochemistry were performed in whole mount preparations. Key Results: Myenteric S neurons from chemotherapy‐treated patients were hyperexcitable; more action potentials (11.4 ± 9.4, p < 0.05) were fired in response to depolarising current pulses than in non‐treated patients (1.4 ± 0.5). The rheobase and the threshold to evoke action potentials were significantly lower for neurons from chemotherapy‐treated patients compared to neurons from non‐treated patients ( p < 0.01). Fast excitatory postsynaptic potential reversal potential was more positive in neurons from chemotherapy‐treated patients ( p < 0.05). An increase in the number of neurons with translocation of Hu protein from the cytoplasm to the nucleus was observed in specimens from chemotherapy‐treated patients (103 ± 25 neurons/mm 2, 37.2 ± 7.0%, n = 8) compared to non‐treated (26 ± 5 neurons/mm 2, 11.9 ± 2.7%, n = 12, p < 0.01). An increase in the soma size of neuronal nitric oxide synthase‐immunoreactive neurons was also observed in these specimens. Conclusions & Inferences: This is the first study suggesting functional and structural changes in human myenteric neurons in specimens of colon from patients receiving anticancer chemotherapy. These changes may contribute to the causation of gastrointestinal symptoms experienced by chemotherapy‐treated patients. Abstract : This is the first electrophysiological study of human enteric neurons in fresh colon specimens from colorectal cancer patients treated and untreated with chemotherapeutic agents. Neuronal hyperexcitability and morphological changes in myenteric neurons may contribute to the causation of gastrointestinal symptoms experienced by chemotherapy‐treated patients.